State policies and the warranted growth rate - Jamee K. Moudud (Levy Economics Institute of Bard College, 2002)
This paper raises questions about austerity policies by investigating the effects of the state's tax and expenditure policies on the warranted growth rate. It proposes two mechanisms to raise the warranted growth rate in the event that there is long-run unemployment. First, it incorporates Pasinetti's taxation function into Harrod's growth framework to show how, with an unbalanced budget, an increase in any kind of tax rate, including the tax rate on profits, will raise the warranted path. Such a policy can be accompanied by an increase in aggregate government spending. Second, by introducing a public investment function and, following Keynes, by assuming that the government's expenditures are split into a current and a capital budget, it shows that an increase in capacity-augmenting investment by state enterprises can also raise the warranted path. In other words, judicious tax and expenditure policies provide the basis for increases in government spending, including a greater degree of capacity-augmenting public investment. The paper thus formalizes Keynes's proposals regarding the socialization of investment and shows how this can be accomplished via appropriate compositional changes in government spending and taxation policies.
Keywords: 330